Impact of Routine Point-of-Care Versus Laboratory Testing for Early Infant Diagnosis of HIV: Results From a Multicountry Stepped-Wedge Cluster-Randomized Controlled Trial. (1st July 2020) - Sacks, Emma; Cohn, Jennifer; Ochuka, Bernard; Mafaune, Haurovi; Chadambuka, Addmore; Odhiambo, Collins; Masaba, Rose; Githuka, George; Mahomva, Agnes; Mushavi, Angela; Lemaire, Jean-Francois; Bianchi, Flavia; et al.
Abstract : Background: Although the World Health Organization recommends HIV-exposed infants receive a 6-week diagnostic test, few receive results by 12 weeks. Point-of-care (POC) early infant diagnosis (EID) may improve timely diagnosis and treatment. This study assesses the impact of routine POC versus laboratory-based EID on return of results by 12 weeks of age. Methods: This was a cluster-randomized stepped-wedge trial in Kenya and Zimbabwe. In each country, 18 health facilities were randomly selected for inclusion and randomized to timing of POC implementation. Findings: Nine thousand five hundred thirty-nine infants received tests: 5115 laboratory-based and 4424 POC. In Kenya and Zimbabwe, respectively, caregivers were 1.29 times [95% confidence interval (CI): 1.27 to 1.30, P < 0.001] and 4.56 times (95% CI: 4.50 to 4.60, P < 0.001) more likely to receive EID results by 12 weeks of age with POC versus laboratory-based EID. POC significantly reduced the time between sample collection and return of results to caregiver by an average of 23.03 days (95% CI: 4.85 to 21.21, P < 0.001) in Kenya and 62.37 days (95% CI: 58.94 to 65.80, P < 0.001) in Zimbabwe. For HIV-infected infants, POC significantly increased the percentage initiated on treatment, from 43.2% to 79.6% in Zimbabwe, and resulted in a nonsignificant increase in Kenya from 91.7% to 100%. The introduction of POC EID also significantly reduced the time to antiretroviral therapy initiation by an average of 17.01 days (95% CI: 9.38 to 24.64, P < 0.001) in Kenya and 56.00 days (95% CI: 25.13 to 153.76, P < 0.001) in Zimbabwe. Conclusions: POC confers significant advantage on the proportion of caregivers receiving timely EID results, and improves time to results receipt and treatment initiation for infected infants. Where laboratory-based EID systems are unable to deliver results to caregivers rapidly, POC should be implemented as part of an integrated testing system. Abstract : Supplemental Digital Content is Available in the Text.